Sucesso social, branqueamento e racismo - Lima, Marcus Eugênio Oliveira (2017)
This study investigates the effects of perceived skin colour and of the social success on the whitening and on the infra-humanization. In this sense, white subjects evaluated a group of black people or a group of white people (represented by photographs), which obtained social success or that fail. The design contains two between subject's independent variables (white versus black) and social performance (success versus failure). The results indicate that blacks that obtain social success are perceived as whitener than the blacks that fail. A mediation analysis indicated that as much the blacks with success are whitened, more typically human characteristics are attributed to them. The inverse happens for blacks less whitened. These results are analysed and discussed in according to the theories about racism in Brazil and the new expressions of racism.